Attentional capture by task-irrelevant fearful faces is revealed by the N2pc component - Eimer, Martin (Elsevier Science B.V, 2007)
We measured the N2pc component as an electrophysiological indicator of attentional selection to investigate whether fearful faces can attract attention even when they are entirely task-irrelevant and attention is focused on another demanding visual monitoring task. Participants had to detect infrequent luminance changes of the fixation cross, while ignoring stimulus arrays containing a face singleton (a fearful face among neutral faces, or neutral face among fearful faces) to the left or right of fixation. On trials without a target luminance change, an N2pc was elicited by fearful faces presented next to fixation, irrespective of whether they were singletons or not, demonstrating that irrelevant fearful faces can bias the spatial distribution of attention. The N2pc to fearful faces was attenuated when face arrays were presented simultaneously with a target luminance change, suggesting that concurrent target processing reduces attentional capture by emotional salient events.